Implementation of Cooperative Learning Models: Inside Outside Circle and Quis-Quis Trade to Improve Mathematics Learning Outcomes for Grade V Students at UPT SDN 11 Makale - Reni Lolotandung; Novalia Sulastri (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to describe the implementation of cooperative learning models, namely Inside Outside Circle and Quis-Quis Trade, to improve the mathematics learning outcomes of fifth-grade students at UPT SDN 11 Makale. The research uses a qualitative descriptive method with a classroom action research design. The subjects of this study are 18 fifth-grade students. Data collection techniques include written tests, interviews, and observations. The results of this study indicate an improvement in student learning outcomes after implementing the Inside Outside Circle and Quis-Quis Trade models. The percentage of mastery in the first cycle reached 54.25%, which falls within the good criteria, while in the second cycle, it reached 83.75%, falling within the very good criteria.